Extradural Dorsal Spinal Paraganglioma: A Rare Case Report and Literature Review - Bhaskar, Mukesh K.; Kumar, R.; Singh, Sunil K.; Meel, Mukta (Indian Journal of Neurosurgery, 2018)
Paragangliomas are neuroendocrine tumors originating from specialized cells of neural crest derivative. They are mostly found in the carotid and jugulotympanic region. Paragangliomas are extremely rare in the spine, and in literature, most cases are described as intradural extramedullary lesion in the cauda equine or filum terminale region. Extradural dorsal spine paragangliomas are even rarer, and till date, only 11 cases are reported in available literature. We describe a case of an adult woman who presented with mid dorsal region pain and sensory-motor spastic paraplegia. Imaging features were suggestive of D5 Pott's spine with epidural granulation tissue. Perioperatively, the tumor was moderately vascular and complete excision done. On HPE and IHC, diagnosis of paraganglioma was made. There was no evidence of clinical recurrence of the lesion at 6 months follow-up.
Keywords: paraganglioma; dorsal spine; Zellballen's pattern; immunohisto chemistry